Learning Mathematics in Early Grades - SARMA, T.P (THE PRIMARY TEACHER, 2014)
Children have ideas of many things. Sometimes they can express and sometimes they cannot express because of fear and phobia in their mind. If we give them freedom and listen to their words and encourage them then they can learn many new things with their limited understanding. In this article the author has tried to communicate the experiences which were gained by conducting early mathematics activities with the children of Class I of Kendriya Vidhyalaya Primary School, NCERT Campus, New Delhi.